Effects of fancy rope-skipping on motor coordination and selective attention in children aged 7–9 years: a quasi-experimental study - Deng, Libo; Wu, Hua; Ruan, Hui; Xu, Dan; Pang, Shibo; Shi, Min (Frontiers in Psychology, 2024)
Introduction: Recent studies have emphasized the intricate connection between exercise and cognition, focusing on specific cognitive processes and their correlations with specific motor skills. However, research on the impact of the qualitative aspects of movement on both short- and long-term cognitive performance is limited. In this quasi-experimental study, we investigate the impact of a 10-week fancy rope-skipping intervention on motor coordination and selective attention of 7-9-year-old children. Methods: A total of 60 primary school students from Changbin School in Haikou participated and completed the study from October to December 2022. The 60 participants were divided into a fancy rope-skipping group and a control group. Children’s motor coordination was assessed using the Körperkoordinations Test für Kinder (KTK), while selective attention was evaluated using the d2 Test of Attention. Children were assessed at baseline and after the 10-week intervention. Results: Compared with the control group, the scores for the total KTK and for the hopping for height, jumping sideways, and moving sideways sub-items were significantly higher in the rope-skipping group after the intervention, with a significant interaction effect between time and intervention. Attention concentration improved in the rope-skipping group and had a significant interaction effect between time and intervention compared with the control group; the effects of the intervention on other aspects of selective attention were unclear. Conclusions: Our study suggests that a 10-week fancy rope-skipping intervention may potentially enhance motor coordination and selective attention accuracy in children aged 7–9 years.